ANALISIS KINERJA PINJAMAN USAHA UMKM (Studi Kasus di Koperasi Kabupaten Pekalongan) - Fangela Myas Sari (EKOMBIS: JURNAL FAKULTAS EKONOMI, 2022)
In Indonesia, there are many UMKM or their people who cannot repay loans because some of them are constrained by economic problems, while others have errors on the part of the borrowing bank, namely errors in lending surveys that are still less effective and selective.This study aims to solve problems that exist in Banking and UMKM, namely to examine the effect of Credit Terms and Credit Risk Control on Loan Performance. This research was conducted in a cooperative in Pekalongan Regency. The sample was determined by purposive sampling technique and obtained 35 respondents. Data analysis using Warp PLS Version 8.0. The results of this study indicate that Credit Terms and Credit Risk Control on Loan Performance have a positive and significant effect.